TDO2‐augmented fibroblasts secrete EVs enriched in immunomodulatory Y‐derived small RNA. Issue 2 (2nd February 2023) - Ciullo, Alessandra; Peck, Kiel; Jones, Xaviar; Yamaguchi, Shukuro; Morris, Ashley Anne; Kumar, Arati Naveen; Li, Liang; Lee, Jamie; dos Santos, Rodrigo Miguel; Cingolani, Eugenio; Ibrahim, Ahmed Gamal
Abstract: Mounting evidence implicates extracellular vesicles (EVs) factors as mediators of cell therapy. Cardiosphere‐derived cells are cardiac‐derived cells with tissue reparative capacity. Activation of a downstream target of wnt/β‐catenin signalling, tryptophan 2, 3 dioxygenase (TDO2) renders therapeutically inert skin fibroblasts cardioprotective. Here, we investigate the mechanism by which concentrated conditioned media from TDO2‐augmented fibroblasts (TDO2‐CCM) exert cardioprotective effects. TDO2‐CCM is cardioprotective in a mouse model of MI compared to CCM from regular fibroblasts (HDF‐CCM). Transcriptomic analysis of cardiac tissue at 24 h demonstrates broad suppression of inflammatory and cell stress markers in animals given TDO2‐CCM compared to HDF‐CCM or vehicle. Sequencing analysis of TDO2‐EV RNA demonstrated abundance of a small Y‐derived small RNA dubbed 'NT4'. Purification of TDO2‐EVs by size‐exclusion chromatography and RNAse protection assays demonstrated that NT4 is encapsulated inside EVs. Consistently with TDO2‐CCM, macrophages exposed to NT4 showed suppression of the inflammatory and cell stress mediators, particularly p21/cdkn1a. NT4‐depleted TDO2‐CCM resulted in diminished immunomodulatory capacity. Finally, administration of NT4 alone was cardioprotective in an acute model of myocardial infarction. Taken together, these findings elucidate the mechanism by which TDO2 augmentation mediates potency in secreted EVs through enrichment of NT4 which suppresses upstream cell stress mediators including p21/cdkn1a. Abstract : Activation of tryptophan 2, 3‐dioxygenase in a therapeutically inert cell type triggers secretion of cardioprotective EVs. These EVs are laden with a Y‐derived small RNA which mediates the therapeutic effect through suppression of p21‐p16 pro‐senescent signalling in macrophages to attenuate inflammatory activation.